Business and Management Studies in the 2014 Research Excellence Framework. (17th June 2015) - Pidd, Michael; Broadbent, Jane
<x xml:space="preserve">Abstract</x> The Research Excellence Framework 2014 (REF 2014) was the 7th formal assessment of research in UK universities and other institutions of higher education. Participation in these assessments is voluntary, and institutions can decide which staff to include and under which discipline to include them. A hundred and one institutions chose to submit research in Business and Management Studies, and this work was assessed by a panel of academic researchers and research users nominated by a wide range of academic constituencies. The previous assessment exercise was conducted in 2008, and REF 2014 shows that the quality of UK research in Business and Management Studies, already high in 2008, has improved since then. The operation of the Business and Management Studies sub‐panel is described, the results are summarized, and a few caveats are discussed so as to aid the Business and Management Studies community in its endeavours to understand and evaluate the process and the results.